1994
DOI: 10.1080/07900629408722620
|View full text |Cite
|
Sign up to set email alerts
|

Water resources development of the Indo‐Nepal region

Abstract: There is no difference of opinion about the idea that development of water and hydroelectric power resources in the Indo-Nepal region would be of substantial mutual benefit to both countries. Any development in the region of Nepal and the Indian States of Uttar Pradesh and Bihar would be of considerable benefit to the people, as this region is one of the poorest in the world. Large projects have been discussed between the two countries for several decades. However, none of these projects has reached even the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The sediments form a thick set of unconfined and leaky aquifers at 1,500 to 2,000 m below ground level (bgl) with a varying proportion of sand, gravel and pebbles, and contain several layers of high-yielding aquifers (Prasad 1990;Rao and Prasad 1994). The few outcrops of consolidated formations can be seen in the north, west and northeast boundaries of the basin (CGWB 2011).…”
Section: Hydrogeologymentioning
confidence: 97%
“…The sediments form a thick set of unconfined and leaky aquifers at 1,500 to 2,000 m below ground level (bgl) with a varying proportion of sand, gravel and pebbles, and contain several layers of high-yielding aquifers (Prasad 1990;Rao and Prasad 1994). The few outcrops of consolidated formations can be seen in the north, west and northeast boundaries of the basin (CGWB 2011).…”
Section: Hydrogeologymentioning
confidence: 97%
“…Hydrogeologically, the basin is filled with thick alluvial sediments deposited by the river and its distributaries. It forms a thick set (varies from 1,500 to 2,000 m bgl (below ground level)) of unconfined and leaky aquifers with varying proportions of sand, gravel, and pebbles with several layers of highyielding aquifers (Prasad 1994;MacDonald et al 2015). A few rocky exposures can be seen in the basin margins (north, west, and north-east) (CGWB 2011).…”
Section: Geology and Hydrogeologymentioning
confidence: 99%
“…According to CGWB (2011), litho-units of Bihar are grouped as unconsolidated/alluvial formations, semi-consolidated formations and consolidated/fissured formations. Lithology of North Bihar shows that very deep alluvial deposits, from 1,500 to 2,000 m, with several layers of high-yielding aquifers exist in this region (Rao and Prasad 1994). These are in semi-confined and confined conditions, generally overlain by very thick unconfined aquifers.…”
Section: Biharmentioning
confidence: 99%
“…The river's transport capacity may at times be exceeded due to the relatively high sediment yields from basins that alternate between dry and wet seasons (Wells and Dorr 1987). Rao and Prasad (1994) reported that Koshi and Gandak rivers, formed from snowmelt, have constant interaction with groundwater, which contributes to a substantial part of the flow of these rivers during the non-monsoon period. Groundwater found in the Terai region is both under confined and unconfined conditions.…”
Section: Groundwater Potential and Challengesmentioning
confidence: 99%
See 1 more Smart Citation